Analisis Faktor-Faktor Yang Mempengaruhi Pengangguran Di Provinsi Jawa Tengah Tahun 2012-2014 Dengan Metode Panel Data - NUGRAHA, FARID; , Eni Setyowati, S.E, M.Si (2017)
This study aims to find out how the influence of inflation, education level, investment and economic growth on unemployment in Central Java Province. This research is a quantitative research using panel data, the data used in the form of time series (2012-2014) and cross section (35 regencies in Central Java province). The type of data used in this study is secondary data obtained from the Central Bureau of Statistics (BPS) and the journal as a supporter. The results show that Fixed Effect Method (FEM) is the most appropriate model. Based on the results of F test, the results if the data variable inflation, and economic growth affect the unemployment in the Province of Central Java in 2012-2014. The result of determinant coefficient test (R2) shows that the R-square value is 0.909922, meaning 90.99% variation of unemployment variable can be explained by inflation, education, investment, and economic growth variable. While the remaining 9.01% is explained by other variables not included in the model. Based on the test of the validity of the influence (t test) on the significance (α) of 0.1, the inflation variable, and economic growth have a significant positive effect on unemployment, while education and investment variables have no effect on unemployment in Central Java Province 2012-2014.